Measurement and assessment of social support in hospitalized patients undergoing chemotherapy - Zielińska-Więczkowska, Halina; Betłakowski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2010)
Background: The aim of the study was to measure and assess social support in hospitalized cancer patients undergoing chemotherapy. Material and methods: The study included 182 cancer patients of the Oncology Center, Bydgoszcz, and was conducted between September 2008 and June 2009. Patients with the diagnosis of cancer before starting the chemotherapy treatment (n = 77, group A – comparative group) were examined first. Then a group of patients undergoing standard chemotherapy in hospital was examined (n = 105, group B – the examined group). Social Support Scale by Zarzycka (SSS) was used for measurement and assessment of the social support. Results: Mean of social support in patients in the diagnostic phase, before starting chemotherapy, was 14.43, whereas in patients undergoing chemotherapy it was 14.97. Majority of patients in both groups received social support at medium high and medium low levels. Of all examined determinants of social support, time flexibility of family members received the highest values from the patients (group B – mean 2.59; group A – mean 2.55). Patients who did not have enough money to meet their basic needs, as well as divorced and widowed people received the least amount of support (group B – mean 2.13; group A – mean 1.55, 1.67 and 1.88 respectively). Conclusions: Patients undergoing chemotherapy received more support than patients in the diagnostic phase. Significant determinants of social support received by cancer patients were material status and marital status. The patients’ families were the main source of support.